Cybercrime : protecting your business, your family and yourself - Wade, Todd (BCS, The Chartered Institute for IT, 2022)
Cybercrime is a sad, ever-developing reality of our digital lives. Cybercriminals are ruthless and know how to use persuasion and manipulation to get what they want. We are all in danger of falling victim to their tricks, which can lead to serious consequences for our business, our family and ourselves.This book aims to prepare you to defend yourself against the tactics cybercriminals use, and gives you advice on what you can do if you, or your business, does fall victim to cybercrime. With a focus on cyber fraud and cyber extortion, this book explores cybercrime from attack methods to impact, with the use of real-world case studies alongside practical suggestions on preventative measures, warning signs of cybercrime and next steps if you find yourself a victim.